Faktor-Faktor yang Berhubungan dengan Hasil Pra Skrining Perkembangan Anak Usia 60-72 Bulan di Telanaipura Kota Jambi Tahun 2016 - Indarmien Netty Ariasih; ajeng Galuh Wuryandari (Poltekkes Kemenkes Jambi, 2017)
Abstrak Latar belakang: Masa anak prasekolah (usia 60-72 bulan) adalah masa yang sensitif terjadi penyimpangan pertumbuhan dan perkembangan, masa dimana anak dipersiapkan untuk sekolah, karena itu panca indra dan sistem reseptor penerima rangsang serta proses memori sudah harus siap, sehingga anak mampu belajar dengan baik. Belum diketahui nya hasil deteksi dini penyimpangan perkembangan anak di tingkat Pendidikam Usia Dini pada level TK (usia 60-72 bulan) yang menggunakan Kuesioner Pra Skrining Perkembangan (KPSP) di Telanaipura Jambi Metode :Penelitian Observasional menggunakan rancangan cross sectional study. Populasi pada penelitian ini adalah seluruh ibu dan anak prasekolah yang bersekolah di PAUD / TK yang ada di Kecamatan Telanaipura Kota Jambi pada bulan Juni 2015. Sampel dalam penelitian ini adalah ibu dan anak yang memenuhi kriteria inklusi. Dari seluruh anak prasekolah berusia 60-72 bulan yang ada di Kecamatan Telanaipura dipilih 147anak yang bersekolah di TK Al Mutaqin dan TK Nurul Ilmi. Analisis yang dilakukan dalam penelitian ini adalah distribusi frekuensi dan Chi-square.Kesimpulan: Variabelyang berpengaruh terhadap hasil skrining perkembangan anak prasekolah adalah status gizi anak, sedangkan jenis kelamin anak, tingkat pendidikan ibu dan status pekerjaan ibu tidak memiliki pengaruh terhadap hasil skrining perkembangan anak pra sekolah. Abstrack Factors associated with pre-screening outcomes for children aged 60-72 months in Telalanipura Jambi City year 2016 Background: The early years of life is a period that full of opportunities to grow and susceptible to danger. A stage of child development is formed by the source of resistance and vulnerable. The preschoolers period (ages 60-72 months) is a sensitive period of deviation of growth and development, during this time children are prepared for school, thus their sense and excitatory receptor system receiver and memory processes must be prepared, to help children be able to learn well. It should be noted that the learning process at this time is by playing. Parents and families are expected to monitor and detect the growth and the development of their children, so that early intervention can be done when the child has an abnormalities and disturbances, so that the child's development can be optimized .At the age of 60-72 months is a childhood preschool, growth period are stable.The results has not been known yet of Early detection of developmental disorders of children in Early Childhood Education level at kindergarten level (age 60-72 months) using a Pre Screening Questionnaire Development (KPSP) in Jambi TelanaipuraMethode: this research is cross sectional study. The population of this research is a Mother and their preschooler’s children who already went to Playgroup/kindergarten in the Telanai Pura District, Jambi City on June 2015. The samples of this research are mother and their children who fulfill the inclusion criteria. From all the preschooler chil-dren ages 60-72 months in Telanai Pura District, researcher choose 147 children went to Al Mutaqin Kindergarten and Nurul Ilmi Kindergarten.The analysis in this research is distribution frequency and Chi-square.Conclusion:The variable that related tothe prescreening result of preschooler children development is children nutrient status, while children’s gender, mother’s education level and mother’s working status does not have any relation to the prescreening result of pre-schooler children development.